Hak Privasi Pasien HIV dan Kewajiban Negara: Analisis Yuridis Perlindungan Data Kesehatan Sensitif (Pusat Riset dan Inovasi Nasional, 2026)
The right to privacy and the right to health are fundamental human rights that are closely interconnected. The protection of privacy for patients with Human Immunodeficiency Virus (HIV) constitutes a critical issue, given that HIV status is classified as highly sensitive health data and is particularly vulnerable to stigma and discrimination. In Indonesia, the legal framework governing the protection of HIV patients’ health data has been normatively strengthened through the Personal Data Protection Law and the Health Law; however, its implementation continues to face various challenges. This article aims to analyze the right to privacy of HIV patients and the obligations of the state in protecting sensitive health data, as well as to examine the limitations and exceptions to the disclosure of HIV-related data within the framework of law and human rights. This study employs a normative legal research method using statutory, conceptual, and human rights-based approaches. Legal materials are analyzed qualitatively through juridical interpretation and prescriptive analysis. The findings indicate that HIV status is legally categorized as sensitive personal data that is entitled to a high level of legal protection. The state bears tripartite obligations to respect, protect, and fulfill the privacy rights of HIV patients. Nevertheless, a gap persists between legal norms and their implementation, particularly in the management of electronic medical records. The protection of HIV patients’ privacy rights requires strengthened legal implementation, regulatory harmonization, and the adoption of a human rights-based approach to ensure that data protection does not conflict with public health interests.